Liberalism, nationalism and religion: Multidimensional autonomy, trade‐offs and analogies. Issue 3 (27th April 2022) - Wittrock, Jon
Abstract: This article aims to provide a conceptual framework for exploring the relations between liberal nationalism and religion. Combining multidimensional analyses of autonomy as well as religion, the article aims to provide a framework for considering, with greater precision, different potential versions of liberal nationalism, and which kinds of prioritisations and trade‐offs they would involve. Religion is approached in terms of Wittgensteinian family resemblances, referring to a host of overlapping narratives, norms, objects and practices. Autonomy is analysed in terms of collective and individual autonomy, and the latter is divided into four major dimensions: liberty (freedom from coercion) opportunity (available options) capacity (for making choices) and authenticity (the degree to which choices are genuine). These, furthermore, may be distributed differently across space and time: for example, liberty may be restricted in the present to preserve it over time. Liberal nationalism ultimately has to balance intrinsic and instrumental arguments, while respecting human rights.